PENGARUH PENGALAMAN BELANJA ONLINE DAN KEPERCAYAAN TERHADAP MINAT BELI ULANG DI TIKTOK SHOP (STUDI KASUS MAHASISWA MANAJEMEN UNIVERSITAS KRISTEN INDONESIA TORAJA) - Katampanan, Soma Edy; Althon Pongtuluran; Astriwati Biringkanae (STIE-PMCI, 2023)
This study aims to analyze the effect of shopping experience and consumer trust on repurchasing intentions in the TikTok Shop application, a study conducted on management students at the Indonesian Christian University of Toraja. The research method used is quantitative research with a sampling technique that is a saturated sample and obtained a total sample of 55 respondents. Data was collected using a questionnaire and then analyzed using multiple linear regression and the data was processed with the help of the SPSS (Statistics Program For Social Science) statistical application. The results showed that the online shopping experience had a significant positive effect on repurchase intention with a sig value of 0.00<0.05 and the trust variable had a significant effect on repurchase intention with a sig value of 0.03<0.05. Simultaneously, online shopping experience and trust influence repurchase intention with a sig value of 0.00<0.05. It is important for Tiktok Shop managers to maintain consumer confidence in order to increase consumer surplus every year